Immune response of blue mussels (Mytilus edulis) in spawning period following exposure to metals - M. Fraser; P. Rault; M. Fortier; P. Brousseau; M. Fournier; C. Surette; C. Vaillancourt (MDPI AG, 2014)
Not available